2014
DOI: 10.1108/ijhcqa-01-2013-0001
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination strategy for Lean thinking in health care

Abstract: There are many case studies describing Lean implementation in single healthcare organisations, but little is known about effective dissemination and implementation strategies in large healthcare systems. The authors, therefore, suggest activities for developing and implementing dissemination strategies in multiple healthcare organisations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…The findings in this review correlate with conclusions by many authors. They also found that in health care lean production has been reduced to the use of specific elements and tools to improve efficiency and quality of care (Dannapfel et al., ; Fillingham, ; Holden et al., ; Kim et al., ; Radnor et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings in this review correlate with conclusions by many authors. They also found that in health care lean production has been reduced to the use of specific elements and tools to improve efficiency and quality of care (Dannapfel et al., ; Fillingham, ; Holden et al., ; Kim et al., ; Radnor et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Radnor et al. () state that most health care organisations are still at an adoption stage equivalent to the late 1980s and early 1990s in automotive manufacturing, restricted to elements such as specific tools and techniques (Dannapfel, Poksinska, & Thomas, ; Fillingham, ; Holden, Eriksson, Andreasson, Williamsson, & Dellve, ; Kaplan, Patterson, Ching, & Blackmore, ; Kim, Spahlinger, Kin, & Billi, ; Radnor et al., ). Consequently, sustainability activities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has already been demonstrated that Lean is often reduced in health care to the use of tools and/or a limited amount of integrated Lean principles (Dannapfel, Poksinska, & Thomas, ; Holden, Eriksson, Andreasson, Williamsson, & Dellve, ; Radnor, Holweg, & Waring, ).…”
Section: Discussionmentioning
confidence: 99%
“…Such employee effects are also summed up by White et al [36]. Cooperation is a desired effect but seems to be a complicated one to achieve according to Seddon et al [35] and O'Brien & Boat [37] Improving the entire system, and not just individual departments remains a major challenge [38]. Lean Health-care can foster interdisciplinary cooperation because everybody in the organization needs to be involved [37].…”
Section: What Effects Of Lean Are Described In Research?mentioning
confidence: 99%